Effects of functional exercises in the warm-up on sprint performances - Sander, A.; Keiner, M.; Schlumberger, A.; Wirth, K.; Schmidtbleicher, D. (The Journal of Strength and Conditioning Research, 2013)
The process of warming up prepares athletes for subsequent stress and increases their level of performance. Functional exercises are often included in warm-up programs for power sports, although a positive effect of functional exercises has not been confirmed. The aim of this study was to measure a possible effect of functional exercises on sprint performance included in a warm-up program. A total of 121 elite youth soccer players between 13 and 18 years of age participated in this study and performed 2 different warm-up programs. The first program (NWP) consisted of 5 minutes of nonspecific running, coordination exercises, stretching, and acceleration runs. The second program (WPS) was the same with additional functional exercises. The subjects were tested performing linear sprints of approximately 30 m and change-of-direction sprints of approximately 10 m. The t-test for dependent samples showed significant differences between the groups for each segment of the linear sprint (p < 0.01 for 5 m; p < 0.001 for 10, 15, 20, 25, and 30 m); however, the effect sizes are small. Also, in the change-of-direction sprint, the t-test showed significant differences between the groups (p < 0.01 for 10 m left, 10 m right; p < 0.001 for 5 m right). These effect sizes are also small. In the change-of-direction sprint time for 5 m left, the data showed no significant differences between the groups. The results show no effects of functional exercises on sprint performance that are implemented in addition to a general warm-up. It appears that a general warm-up program, such as the NWP, generates sufficient activation of the performance-limiting muscles for sprint performance. Functional exercises did not lead to a supplemental activation with a positive effect on sprint performance. Therefore, a warm-up for sprint performance should contain nonspecific running, coordination exercises, stretching exercises, and acceleration runs. These components lead to sufficient activation of the muscles involved in sprint performance. Coaches should use the limited time available for warm-up to work efficiently. The recommendation for warm-up is to pass on functional exercises that have no additional effect in enhancing performance.